Pelayanan Sosial Sebagai Upaya Pemenuhan Keberfungsian Sosial Disabilitas Netra di UPTD Rumoh Seujahtera Beujroh Meukarya (RSBM) Ladong Aceh Besar - Wirda Amalia; Safrizal; Teuku Zulyadi (Jurnal Intervensi Sosial, 2024)
Unlike normal people in general, people with visual impairment experience limitations in carrying out daily activities. In Indonesia, the number of disabilities in 2022 reached 1.5% or around 4 million people. One way to fulfill the social functioning of blind disabilities is to increase motivation and develop potential through rehabilitation at UPTD Rumoh Seujahtera Beujroh Meukarya (RSBM). This study aims to determine what forms of social services for visual disabilities at UPTD RSBM. The type of research used is a qualitative approach with descriptive methods through observation, documentation, and interviews with 5 informants. The results of this study obtained data that the form of social services is in the form of residential rehabilitation social services (Boarding) with several activities such as: Care and nurturing, mental and spiritual guidance, physical guidance, social guidance and psycho social counseling, skills guidance and accessibility services such as massage massage skills, braille reading and writing skills, rattan weaving skills, art skills, jaws computer technology skills, social assistance and resocialization guidance.